Application of Picosecond Laser in Dermatology - Bintanjoyo, Lunardi; Indramaya, Diah Mira (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2023)
ABSTRACT Background: Lasers are one of the most important treatment modalities in dermatology. Lasers interact with chromophores through several mechanisms that depend on fluence and pulse durations. Early lasers worked by photothermal interaction with pulse durations of 1 microsecond to 1 second. A picosecond laser is developed to confine photothermal effects and produce photomechanical effects and plasma induction. Purpose: To understand the mechanism of action and application of picosecond lasers for dermatological disorders. Review: Non-fractional picosecond lasers work by photomechanical interaction. Photomechanical interaction happens when pulse duration is less than inertial confinement time, causing fractures of chromophores with lower energy, or "cold ablation”. Fractional picosecond lasers work by laser-induced optical breakdown (LIOB). In LIOB, accelerated seed electrons cause an electron avalanche that produce a collection of free electrons called plasma, which ablates tissues. LIOB in the skin is always followed by photodisruption. In LIOB, vacuoles and debris were eliminated transdermally and dermal collagen and elastin increased. Picosecond laser may be applied in disorders requiring destruction of chromophores and for collagen and elastin disorders. It is currently the first-line treatment for tattoo removal (Nevus of Ota and Acquired Bilateral Nevus of Ota-like macules, or ABNOM). It has good efficacy and safety for solar lentigines, freckles, and cafe-au-lait macules (CALM). It is an additional treatment for moderate to severe melasma and hypertrophic scars, in combination with other treatments. The fractional picosecond laser showed moderate improvement and low risk of postinflammatory hyperpigmentation (PIH) for atrophic acne scars and produced improvement in striae alba.